Competing trade mechanisms and monotone mechanism choice - Eberhard Feess; Christian Grund; Markus Walzl; Ansgar Wohlschlegel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
We analyze mechanism choices of competing sellers with private valuations and show the existence of monotone pure strategy equilibria where sellers with higher reservation value choose mechanisms with a lower selling probability and a larger revenue in case of trade. As an application we investigate the choice between posted prices and auctions and demonstrate that sellers refuse to offer posted prices as long as (risk-neutral) buyers do not differ with respect to their transaction costs in both trade institutions. If some buyers have lower transaction costs when trading at a posted price, it is optimal for sellers to offer posted prices if and only if they have a sufficiently high reservation value. We develop an empirical strategy to estimate revenues of posted prices and auctions that takes selling probabilities explicitly into account, and confirm our theoretical predictions with data from the EURO 2008 European Football Championship.
Keywords: D43; D44; D82; L13; 330; Competing Sellers; Single-Crossing; Auctions; Fixed Prices